Involvement of a battery of investigated genes in lipid droplet pathophysiology and associated comorbidities - Sami N. Al Harake; Yasamin Abedin; Fatema Hatoum; Nour Zahraa Nassar; Ali Ali; Aline Nassar; Amjad Kanaan; Samer Bazzi; Sami Azar; Frederic Harb; Hilda E. Ghadieh (Adipocyte, 2024)
Lipid droplets (LDs) are highly specialized energy storage organelles involved in the maintenance of lipid homoeostasis by regulating lipid flux within white adipose tissue (WAT). The physiological function of adipocytes and LDs can be compromised by mutations in several genes, leading to NEFA-induced lipotoxicity, which ultimately manifests as metabolic complications, predominantly in the form of dyslipidemia, ectopic fat accumulation, and insulin resistance. In this review, we delineate the effects of mutations and deficiencies in genes — CIDEC, PPARG, BSCL2, AGPAT2, PLIN1, LIPE, LMNA, CAV1, CEACAM1, and INSR — involved in lipid droplet metabolism and their associated pathophysiological impairments, highlighting their roles in the development of lipodystrophies and metabolic dysfunction.